(3JgGaJ GdadGSaIs - (3Ydj Hf eMeO GdWhSj GdHJGQcGfj, YdGA GdOjf,J (B877 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf LedI GdBQGA JWGHbJ hLdI GdYbdGA JhGabJ s
(3BNQgG (B:s
(3Cf GdYbd djS eSJbdkG ai GOQGc GdCehQ GdEdgjI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B9 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B185s
Keywords: (3GdadSaI hGdefWbs